Real-World Validity of Tissue-Agnostic Circulating Tumor DNA Response Monitoring in Lung Cancers Treated With Chemotherapy, Immunotherapy, or Targeted Agents - Anne C. Chiang, MD, PhD; Russell W. Madison, MS; Zoe June Assaf, PhD; Alexander Fine, PhD; Yi Cao, PhD; Ole Gjoerup, PhD; Yanmei Huang, PhD; Dexter X. Jin, PhD; Jason Hughes, PhD; Vladan Antic, MD, PhD; Amanda Young, PhD; David Fabrizio, MS; et al. (JTO Clinical and Research Reports, 2025)
Introduction: Circulating tumor DNA (ctDNA) monitoring is emerging as a minimally invasive complement to tumor imaging. We evaluated the validity of tissue-agnostic ctDNA quantification across four treatment modalities in NSCLC and SCLC. Methods: Data from consenting patients were collected from electronic health records as part of the Prospective Clinico-Genomic study (NCT04180176). ctDNA tumor fraction (TF) was retrospectively calculated for plasma collected six to 15 weeks after therapy initiation. TF dynamics were compared among an exploratory cohort, NSCLC and SCLC validity cohorts, and by therapy class. Results: In on-treatment plasma, undetectable TF was associated with longer real-world progression-free survival and real-world overall survival in exploratory (21.8 versus 8.8 mo; hazard ratio [HR] = 0.35, 95% confidence interval [CI]: 0.24–0.50), validity NSCLC (23.5 versus 9.5 mo; HR = 0.34, 95% CI: 0.22–0.53), and validity SCLC (15.9 versus 8.3 mo; HR = 0.19, 95% CI: 0.08–0.42) cohorts. Equal to or greater than 90% and equal to or greater than 50% TF reduction from baseline was also associated with significantly improved outcomes. ctDNA dynamics differed by treatment class: TF reported greater discriminatory power for selecting tumor responses to immunotherapy and targeted therapy (≥50% decrease in 91% of responders versus 24% of nonresponders) than chemotherapy and chemo-immunotherapy (86% versus 60%). TF dynamics correlated with outcomes, but models of real-world progression-free survival and real-world overall survival were improved when tumor response was included. Conclusions: Tissue-agnostic monitoring of molecular response on the basis of ctDNA TF dynamics has utility in the real-world setting across four different treatment regimens. These results suggest that ctDNA dynamics may be complementary to tumor imaging in both NSCLC and SCLC to better inform patient care.